Circulating cell‐free DNA species affect the risk of hepatocellular carcinoma in treated chronic hepatitis B patients. Issue 3 (16th December 2020) - Papatheodoridi, Alkistis; Chatzigeorgiou, Antonios; Chrysavgis, Lampros; Lembessis, Panagiotis; Loglio, Alessandro; Facchetti, Floriana; Cholongitas, Evangelos; Koutsilieris, Michael; Lampertico, Pietro; Papatheodoridis, George
Abstract: Hepatocellular carcinoma (HCC) may still develop in chronic hepatitis B (CHB) patients even under effective long‐term oral antiviral therapy, but its pathogenesis in the setting of long‐standing inhibition of viral replication has not been completely elucidated. We investigated whether species of circulating cell‐free DNA (cfDNA) may be involved in the process of hepatocarcinogenesis in treated CHB patients. Serum samples were obtained from HBeAg‐negative CHB patients with (HCC cases, n  = 37) or without HCC development during the first 5 years of oral antiviral therapy (controls, n  = 74). HCC cases and controls were matched 1:2 for age, sex and platelets. Determination of different circulating cfDNA species (before HCC diagnosis in HCC cases) including total cfDNA quantity, levels of Alu repeat DNA and RNase P coding DNA, copies of mitochondrial DNA and levels of 5‐methyl‐2′‐deoxycytidine as an indicator of DNA methylation was performed. HCC cases compared with controls had higher median levels of Alu247 (123 vs 69 genomic equivalent, p  = .042) and RNase P coding DNA (68 vs 15 genomic equivalent, p  < .001). In contrast, median cfDNA concentration, Alu115 levels, Alu247/Alu115 ratio as an index of DNA integrity and mitochondrial DNA copies did not differ significantly between HCC cases and controls. Receiver operating characteristic curve analysis showed that levels RNase P coding DNA offered good prediction of subsequent HCC development (c‐statistic: 0.80, p  < .001). In conclusion, serum levels of RNase P coding DNA are increased years before HCC diagnosis and could be potentially helpful in the prediction of the HCC risk in treated HBeAg‐negative CHB patients.